Lithium nickel cobalt aluminate positive electrode material as well as preparation method and application thereof

Through step-by-step solid phase mixing and multi-step calcination, the problem of uneven distribution of aluminum ions in the nickel-cobalt lithium aluminate positive electrode material is solved, uniform mixing of nickel-cobalt-aluminum elements is achieved, and the specific capacity and cycling performance of the positive electrode material are improved.

CN119905498APending Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311415485.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, when preparing nickel-cobalt lithium aluminate (NCA) positive electrode material, aluminum ions are unevenly distributed, resulting in poor spherical shape and loose structure, affecting electrochemical performance.

Method used

The method of step by step solid phase mixing combined with multi-step calcining is adopted. The nickel hydroxide and the aluminum source are first mixed in solid phase, then mixed with the cobalt source for heat treatment, and finally mixed with the lithium source for a second heat treatment, controlling the feeding sequence and heat treatment conditions to achieve uniform mixing of elements.

Benefits of technology

The uniform mixing of nickel, cobalt, aluminum elements is achieved, and the formation of LiAlO2 heterogeneous phases is avoided, and the specific capacity and cycle performance of the positive electrode material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905498A_ABST
    Figure CN119905498A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium nickel cobalt aluminate positive electrode material and a preparation method and application thereof, and the method comprises the following steps: S1, carrying out first solid phase mixing on nickel hydroxide and an aluminum source to obtain a first solid material; s2, carrying out second solid phase mixing on a cobalt source and the first solid material, and carrying out first heat treatment on the obtained mixed material in a first oxygen-containing atmosphere to obtain a second solid material; and S3, carrying out third solid phase mixing on a lithium source and the second solid material, and carrying out second heat treatment on the obtained mixed material in a second oxygen-containing atmosphere. The method disclosed by the invention is simple in steps, adopts a method of combining step-by-step solid-phase mixing with multi-step roasting, and can not only realize batch production of the lithium nickel cobalt aluminate positive electrode material with any component, but also promote uniform mixing of three elements of nickel, cobalt and aluminum by controlling a specific charging sequence and a sequence of solid-phase mixing and heat treatment; therefore, the lithium nickel cobalt aluminate positive electrode material with high specific capacity and good cycle performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of ternary materials for lithium-ion batteries, and in particular, to a nickel-cobalt-aluminum-oxide lithium positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have been widely used in various fields such as transportation, communications, and energy storage. The positive electrode material is the decisive factor in its electrochemical performance and is also the key core of lithium-ion batteries. High-nickel ternary materials have become a hot research material due to their high specific capacity, low overall cost, and stable low-temperature performance. Among them, the representative nickel cobalt aluminum oxide (NCA) material has been widely used in the field of new energy vehicles, but its preparation process still has certain challenges.

[0003] At present, the relatively mature methods for preparing NCA mainly include two kinds. One method is to prepare nickel-cobalt-aluminum precursor by coprecipitation method, and then add lithium source high temperature roasting (such as patent CN101262061A) with appropriate proportion. However, due to the large difference between the precipitation equilibrium constant of aluminum hydroxide and the equilibrium constant of nickel hydroxide and cobalt hydroxide, and aluminum hydroxide will dissolve under alkaline conditions, it is difficult for aluminum ions to form uniform coprecipitation with nickel-cobalt ions, so that aluminum ions are unevenly distributed, and it is easy to cause poor sphericity and loose structure, thereby affecting the electrochemical performance of positive electrode materials. Another method is to prepare nickel-cobalt hydroxide precursor first, then mix with aluminum compound to form coating structure, and then lithiate roasting (such as patent CN1156910A). However, Al2O3 or Al(OH)3 introduced later is easy to form LiAlO2 heterophase with lithium salt, resulting in uneven distribution of each element in NCA, which ultimately affects product performance. Summary of the invention

[0004] The purpose of the present invention is to provide a nickel cobalt aluminum oxide lithium positive electrode material and a preparation method and application thereof.

[0005] In order to achieve the above object, the present disclosure provides a method for preparing a nickel cobalt aluminum oxide positive electrode material in a first aspect, the method comprising the following steps:

[0006] S1, performing a first solid phase mixing of nickel hydroxide and an aluminum source to obtain a first solid material;

[0007] S2, performing a second solid phase mixing of the cobalt source and the first solid material, and performing a first heat treatment on the obtained mixed material under a first oxygen-containing atmosphere to obtain a second solid material;

[0008] S3, performing a third solid phase mixing of the lithium source and the second solid material, and performing a second heat treatment on the obtained mixed material under a second oxygen-containing atmosphere.

[0009] Optionally, the aluminum source includes one or more of aluminum hydroxide, aluminum oxide, aluminum carbonate, aluminum oxalate and aluminum acetate;

[0010] The cobalt source includes one or more of cobalt hydroxide, cobalt oxide, cobalt carbonate, cobalt oxalate and cobalt acetate;

[0011] The lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate.

[0012] Optionally, the first solid-phase mixing, the second solid-phase mixing and the third solid-phase mixing include solid-phase ball milling, and the time is 1-5 hours respectively.

[0013] Optionally, in step S2, the first heat treatment method includes calcination, and the conditions of the first heat treatment include: time of 2-8h and temperature of 400-900°C.

[0014] Optionally, in step S3, the second heat treatment method includes calcination, and the conditions of the second heat treatment include: time of 10-20 hours and temperature of 600-850°C.

[0015] Optionally, the first oxygen-containing atmosphere and the second oxygen-containing atmosphere are oxygen atmosphere or air atmosphere, respectively.

[0016] Optionally, the average particle size of the nickel hydroxide is 5-15 μm.

[0017] A second aspect of the present disclosure provides a lithium nickel cobalt aluminum oxide positive electrode material prepared by the method described in the first aspect of the present disclosure.

[0018] Optionally, the lithium nickel cobalt aluminum oxide positive electrode material comprises a chemical formula of LiNi 1-x-y Co x Al y O2 particles, 0.6≤1-xy<1,0 <x≤0.2,0<y≤0.2。

[0019] A third aspect of the present disclosure provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode, an electrolyte and a negative electrode, the positive electrode comprising the lithium nickel cobalt aluminum oxide positive electrode material described in the second aspect of the present disclosure.

[0020] Through the above technical scheme, the present invention adopts a method of step-by-step solid-phase mixing combined with multi-step calcination. By controlling the specific order of adding materials and the order of solid-phase mixing and heat treatment, it can not only realize the mass production of nickel cobalt aluminum oxide positive electrode materials of any composition, but also promote the uniform mixing of the three elements of nickel, cobalt and aluminum, thereby obtaining a nickel cobalt aluminum oxide positive electrode material with high specific capacity and good cycle performance.

[0021] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0023] Figure 1 This is the electrochemical cycle curve of the nickel cobalt aluminum oxide lithium positive electrode material A3 prepared in Example 3 of the present disclosure.

[0024] Figure 2 This is a scanning electron microscope image of the nickel cobalt aluminum oxide positive electrode material A1 prepared in Example 1 of the present disclosure.

[0025] Figure 3 This is a scanning electron microscope image of the nickel cobalt aluminum oxide positive electrode material D1 prepared in Comparative Example 1 of the present disclosure.

[0026] Figure 4 It is a scanning electron microscope test image and element distribution map of the second solid material in Example 2 of the present disclosure.

[0027] Figure 5 The scanning electron microscope test image and element distribution map of the nickel cobalt aluminum oxide positive electrode material A2 prepared in Example 2 of the present disclosure.

[0028] Figure 6 Electrochemical cycle curves of nickel cobalt aluminum oxide lithium positive electrode materials A1 and D1 prepared in Example 1 and Comparative Example 1 of the present disclosure.

[0029] Figure 7 Electrochemical cycle curves of nickel cobalt aluminum oxide lithium positive electrode materials D3-D6 prepared in comparative examples 3-6 of the present disclosure. DETAILED DESCRIPTION

[0030] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0031] The first aspect of the present disclosure provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, the method comprising the following steps:

[0032] S1, performing a first solid phase mixing of nickel hydroxide and an aluminum source to obtain a first solid material;

[0033] S2, performing a second solid phase mixing of the cobalt source and the first solid material, and performing a first heat treatment on the obtained mixed material under a first oxygen-containing atmosphere to obtain a second solid material;

[0034] S3, performing a third solid phase mixing of the lithium source and the second solid material, and performing a second heat treatment on the obtained mixed material under a second oxygen-containing atmosphere.

[0035] The present invention adopts a method of step-by-step mixing combined with step-by-step heat treatment, firstly solid-phase mixing nickel hydroxide with an aluminum source and a cobalt source in sequence, obtaining nickel cobalt aluminum oxide through a first heat treatment, and then solid-phase mixing the nickel cobalt aluminum oxide with a lithium source, and performing a second heat treatment to obtain a nickel cobalt aluminum oxide positive electrode material; the above method has simple steps, and the migration of cobalt atoms can drive the migration of aluminum atoms, thereby achieving uniform mixing of various elements in the material, avoiding the formation of LiAlO2 impurity phase, and improving the stability of the layered structure. The prepared positive electrode material has good sphericity and Li / Ni mixing degree, and is used as a positive electrode material for a lithium ion battery, having a high specific capacity and good cycle performance.

[0036] In the present disclosure, in order to achieve uniform mixing, in step S1, step S2 and step S3, the first solid phase mixing, the second solid phase mixing and the third solid phase mixing include solid phase ball milling, with the time being 1-5h, preferably 2-4h respectively; solid phase ball milling can be carried out on a planetary ball mill, for example.

[0037] According to one embodiment of the present disclosure, the types of aluminum source, cobalt source and lithium source are all conventional in the art. For example, the aluminum source includes one or more of aluminum hydroxide, aluminum oxide, aluminum carbonate, aluminum oxalate and aluminum acetate. When the aluminum source includes more than two types, their proportion is not specifically limited; the cobalt source includes one or more of cobalt hydroxide, cobalt oxide, cobalt carbonate, cobalt oxalate and cobalt acetate. When the cobalt source includes more than two types, their proportion is not specifically limited; the lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate. When the lithium source includes more than two types, their proportion is not specifically limited.

[0038] According to one embodiment of the present disclosure, the first oxygen-containing atmosphere and the second oxygen-containing atmosphere are respectively an oxygen atmosphere or an air atmosphere, wherein the definitions of the oxygen atmosphere and the air atmosphere are conventional in the art.

[0039] According to one embodiment of the present disclosure, in step S1, the first heat treatment method includes roasting, and the roasting can be carried out in a sagger; the conditions of the first heat treatment include: time is 2-8h, temperature is 400-900℃; preferably, time is 3-7h, temperature is 500-800℃; at this temperature, metal atoms can effectively migrate, thereby promoting uniform dispersion of various elements.

[0040] According to an embodiment of the present disclosure, in step S2, the second heat treatment method includes roasting, and the roasting can be carried out in a sagger; the conditions of the second heat treatment include: time is 10-20h, temperature is 600-850℃; preferably, time is 12-18h, temperature is 700-800℃; the positive electrode material obtained under this condition can exert better capacity and maintain better stability.

[0041] According to one embodiment of the present disclosure, nickel hydroxide has a spherical and / or quasi-spherical morphology, and the above spherical and quasi-spherical shapes are conventionally defined in the art. Preferably, the average particle size of the nickel hydroxide is 5-15 μm; this particle size can better exert the performance of the material and meet the market demand for particle size.

[0042] In the present disclosure, in step S1 and step S2, the amounts of nickel hydroxide, aluminum source and cobalt source are adjusted according to the ratio of Ni, Co and Al in the nickel cobalt aluminum lithium positive electrode material.

[0043] According to one embodiment of the present disclosure, in step S3, the molar ratio of the lithium source calculated as lithium element to the second solid material calculated as the total amount of nickel element, cobalt element and aluminum element can be, for example, (0.8-1.2):1, and the lithium source may be partially lost during the solid phase mixing and heat treatment process.

[0044] A second aspect of the present disclosure provides a lithium nickel cobalt aluminum oxide positive electrode material prepared by the method described in the first aspect of the present disclosure.

[0045] According to one embodiment of the present disclosure, in order to have a higher capacity, the lithium nickel cobalt aluminum oxide positive electrode material includes a chemical formula of LiNi 1-x-y Co x Al y O2 particles, 0.6≤1-xy<1,0 <x≤0.2,0<y≤0.2。

[0046] A third aspect of the present disclosure provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode, an electrolyte and a negative electrode, the positive electrode comprising the lithium nickel cobalt aluminum oxide positive electrode material described in the second aspect of the present disclosure.

[0047] According to one embodiment of the present disclosure, the negative electrode is conventional in the art, and for example may include one or more of a lithium sheet, a carbon material, and a silicon-carbon composite material.

[0048] According to one embodiment of the present disclosure, the electrolyte is conventional in the art, for example, may include one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, lithium hexafluorophosphate and dimethyl carbonate.

[0049] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form.

[0050] The raw materials used in the examples were all purchased from commercial sources and were of analytical grade unless otherwise specified.

[0051] The scanning electron microscope energy spectrum test instrument model is FEIQUANTA400, and the method is that the acceleration voltage is 20kV;

[0052] The X-ray diffraction pattern was tested using an X-ray powder diffractometer from Philips, USA. The method used a Cu target anode Kα radiation source, a step width of 0.02°, a scanning speed of 2° / min, and 2θ=10°-80°.

[0053] Testing method for the chemical formula of positive electrode materials: Inductively coupled plasma mass spectrometry.

[0054] Example 1

[0055] The nickel cobalt aluminum oxide positive electrode material A1 was prepared by the following steps:

[0056] (1) Spherical nickel hydroxide (average particle size of 8.2 μm) and aluminum hydroxide powder were weighed respectively according to a molar ratio of n(Ni):n(Al)=0.8:0.05, and mixed on a planetary ball mill for 2 h to obtain a first solid material;

[0057] (2) according to the molar ratio of n(Ni):n(Co)=0.8:0.15, cobalt acetate was weighed and added to the first solid material, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment in an oxygen atmosphere by roasting at a temperature of 500° C. for 5 hours to obtain a second solid material;

[0058] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, LiOH·H2O and the second solid material were weighed respectively, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a second heat treatment in an oxygen atmosphere by roasting at a temperature of 750°C for 15 hours. The obtained solid product was crushed and sieved to obtain a nickel cobalt aluminum oxide lithium positive electrode material A1 with a chemical formula of LiNi 0.8 Co 0.15 Al 0.05 O2.

[0059] Example 2

[0060] The nickel cobalt aluminum oxide positive electrode material A2 is prepared by the following steps:

[0061] (1) Spherical nickel hydroxide (average particle size of 8.2 μm) and aluminum hydroxide powder were weighed respectively according to a molar ratio of n(Ni):n(Al)=0.8:0.05, and mixed on a planetary ball mill for 2 h to obtain a first solid material;

[0062] (2) cobalt acetate was weighed and added to the first solid material in a molar ratio of n(Ni):n(Co)=0.8:0.15, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment in an oxygen atmosphere by calcination at a temperature of 600° C. for 6 hours to obtain a second solid material;

[0063] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.06:1, LiOH·H2O and the second solid material were weighed respectively, mixed on a planetary ball mill for 3 hours, and then the obtained mixture was put into a sagger and subjected to a second heat treatment in an oxygen atmosphere by roasting at a temperature of 760°C for 18 hours. The obtained solid product was crushed and sieved to obtain a nickel cobalt aluminum oxide lithium positive electrode material A2 with a chemical formula of LiNi 0.8 Co 0.15 Al 0.05 O2.

[0064] Example 3

[0065] The nickel cobalt aluminum oxide positive electrode material A3 was prepared by the following steps:

[0066] (1) Spherical nickel hydroxide (average particle size of 7.7 μm) and aluminum oxide powder were weighed respectively according to a molar ratio of n(Ni):n(Al)=0.7:0.1, and mixed on a planetary ball mill for 2 h to obtain a first solid material;

[0067] (2) cobalt carbonate was weighed and added to the first solid material in a molar ratio of n(Ni):n(Co)=0.7:0.2, mixed on a planetary ball mill for 2 h, and then the obtained mixture was put into a sagger and subjected to a first heat treatment in an oxygen atmosphere by calcination at a temperature of 700° C. for 5 h to obtain a second solid material;

[0068] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.06:1, LiOH·H2O and the second solid material were weighed respectively, mixed on a planetary ball mill for 3 hours, and then the obtained mixture was put into a sagger and subjected to a second heat treatment in an oxygen atmosphere by roasting at a temperature of 760°C for 18 hours. The obtained solid product was crushed and sieved to obtain a nickel cobalt aluminum oxide lithium positive electrode material A3 with a chemical formula of LiNi 0.7 Co 0.2 Al 0.1O2.

[0069] Example 4

[0070] The nickel cobalt aluminum oxide positive electrode material A4 was prepared by the following steps:

[0071] (1) Spherical nickel hydroxide (average particle size of 8.2 μm) and aluminum hydroxide powder were weighed respectively according to a molar ratio of n(Ni):n(Al)=0.8:0.1, and mixed on a planetary ball mill for 2 h to obtain a first solid material;

[0072] (2) according to the molar ratio of n(Ni):n(Co)=0.8:0.1, cobalt acetate was weighed and added to the first solid material, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a first heat treatment in an oxygen atmosphere by roasting at a temperature of 800°C for 6 hours to obtain a second solid material;

[0073] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.08:1, LiOH·H2O and the second solid material were weighed respectively, mixed on a planetary ball mill for 3 hours, and then the obtained mixture was put into a sagger and subjected to a second heat treatment in an oxygen atmosphere by roasting at a temperature of 760°C for 18 hours. The obtained solid product was crushed and sieved to obtain a nickel cobalt aluminum oxide lithium positive electrode material A4 with a chemical formula of LiNi 0.8 Co 0.1 Al 0.1 O2.

[0074] Example 5

[0075] The method of Example 1 is used to prepare a nickel cobalt aluminum oxide positive electrode material A5, except that the aluminum hydroxide in step (1) is replaced by aluminum oxide containing an equal mole of Al element, the cobalt acetate in step (2) is replaced by cobalt oxalate containing an equal mole of Co element, and the LiOH·H2O in step (3) is replaced by lithium carbonate containing an equal mole of lithium element; the chemical formula of the nickel cobalt aluminum oxide positive electrode material A5 is LiNi 0.8 Co 0.15 Al 0.05 O2.

[0076] Comparative Example 1

[0077] The lithium nickel cobalt aluminum oxide positive electrode material D1 was prepared by the following steps:

[0078] (1) Spherical nickel hydroxide (average particle size of 8.2 μm) is placed in a sagger and subjected to a first heat treatment in an oxygen atmosphere by calcination at a temperature of 500° C. for 5 h to obtain a first solid material;

[0079] (2) weighing the first solid material and aluminum hydroxide powder respectively according to a molar ratio of n(Ni):n(Al)=0.8:0.05, mixing them on a planetary ball mill for 2 hours to obtain a second solid material;

[0080] (3) Weighing cobalt acetate and adding it to the second solid material at a molar ratio of n(Ni):n(Co)=0.8:0.15, and mixing them on a planetary ball mill for 2 hours to obtain a third solid material;

[0081] (4) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, LiOH·H2O and the third solid material were weighed respectively, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a second heat treatment in an oxygen atmosphere by roasting at a temperature of 750°C for 15 hours. The obtained solid product was crushed and sieved to obtain a nickel cobalt aluminum oxide lithium positive electrode material D1 with a chemical formula of LiNi 0.8 Co 0.15 Al 0.05 O2.

[0082] Comparative Example 2

[0083] The nickel cobalt aluminum oxide lithium positive electrode material D2 is prepared by the following steps:

[0084] (1) Spherical nickel hydroxide (average particle size of 8.2 μm) and cobalt acetate were weighed respectively according to a molar ratio of n(Ni):n(Co)=0.8:0.15, and mixed on a planetary ball mill for 2 h to obtain a first solid material;

[0085] (2) weighing aluminum hydroxide powder according to a molar ratio of n(Ni):n(Al)=0.8:0.05 and adding it to the first solid material, mixing it on a planetary ball mill for 2 hours, and then putting the obtained mixture into a sagger, and performing a first heat treatment under an oxygen atmosphere by roasting at a temperature of 500°C for 5 hours to obtain a second solid material;

[0086] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, LiOH·H2O and the second solid material were weighed respectively, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a second heat treatment in an oxygen atmosphere by roasting at a temperature of 750°C for 15 hours. The obtained solid product was crushed and sieved to obtain a nickel cobalt aluminum oxide lithium positive electrode material D2 with a chemical formula of LiNi 0.8 Co 0.15 Al 0.05 O2.

[0087] Comparative Example 3

[0088] The nickel cobalt aluminum oxide lithium positive electrode material D3 was prepared by the following steps:

[0089] (1) Spherical nickel hydroxide (average particle size of 8.2 μm) and cobalt acetate were weighed respectively according to a molar ratio of n(Ni):n(Co)=0.8:0.15, and mixed on a planetary ball mill for 2 h to obtain a first solid material;

[0090] (2) weighing aluminum hydroxide according to a molar ratio of n(Ni):n(Al)=0.8:0.05 and adding it to the first solid material, and mixing them on a planetary ball mill for 2 hours to obtain a second solid material;

[0091] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, LiOH·H2O and the second solid material were weighed respectively, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and heat-treated under an oxygen atmosphere by roasting at a temperature of 750°C for 15 hours. The obtained solid product was crushed and sieved to obtain a nickel cobalt aluminum oxide lithium positive electrode material D3 with a chemical formula of LiNi 0.8 Co 0.15 Al 0.05 O2.

[0092] Comparative Example 4

[0093] The nickel cobalt aluminum oxide lithium positive electrode material D4 was prepared by the following steps:

[0094] (1) Spherical nickel hydroxide (average particle size of 8.2 μm) and aluminum hydroxide powder were weighed respectively according to a molar ratio of n(Ni):n(Al)=0.8:0.05, and mixed on a planetary ball mill for 2 h to obtain a first solid material;

[0095] (2) weighing cobalt acetate and adding it to the first solid material at a molar ratio of n(Ni):n(Co)=0.8:0.15, and mixing them on a planetary ball mill for 2 hours to obtain a second solid material;

[0096] (3) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, LiOH·H2O and the second solid material were weighed respectively, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and heat-treated under an oxygen atmosphere by roasting at a temperature of 750°C for 15 hours. The obtained solid product was crushed and sieved to obtain a nickel cobalt aluminum oxide lithium positive electrode material D4 with a chemical formula of LiNi 0.8 Co 0.15 Al 0.05 O2.

[0097] Comparative Example 5

[0098] The nickel cobalt aluminum oxide lithium positive electrode material D5 was prepared by the following steps:

[0099] (1) Spherical nickel hydroxide (average particle size of 8.2 μm), cobalt acetate and aluminum hydroxide powders were weighed respectively according to a molar ratio of n(Ni):n(Co):n(Al)=0.8:0.15:0.05, and mixed on a planetary ball mill for 4 hours to obtain a first solid material;

[0100] (2) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, LiOH·H2O and the first solid material were weighed respectively, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and heat-treated under an oxygen atmosphere by roasting at a temperature of 750°C for 15 hours. The obtained solid product was crushed and sieved to obtain a nickel cobalt aluminum oxide lithium positive electrode material D5 with a chemical formula of LiNi 0.8 Co 0.15 Al 0.05 O2.

[0101] Comparative Example 6

[0102] The following steps were used to prepare the lithium nickel cobalt aluminum oxide positive electrode material D6:

[0103] According to the molar ratio of n(Ni):n(Co):n(Al)=0.8:0.15:0.05, spherical nickel hydroxide (average particle size of 8.2 μm), cobalt acetate and aluminum hydroxide powder were weighed respectively, and then LiOH·H2O was added according to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1. After mixing for 6 hours on a planetary ball mill, the obtained mixture was put into a sagger and heat-treated in an oxygen atmosphere by roasting at a temperature of 750°C for 15 hours. The obtained solid product was crushed and sieved to obtain nickel cobalt aluminum oxide lithium positive electrode material D6, with a chemical formula of LiNi 0.8 Co 0.15 Al 0.05 O2.

[0104] Comparative Example 7

[0105] The following steps were used to prepare the lithium nickel cobalt aluminum oxide positive electrode material D7:

[0106] (1) According to the molar ratio of n(Ni):n(Co):n(Al)=0.8:0.15:0.05, spherical nickel hydroxide (average particle size of 8.2 μm), cobalt acetate and aluminum hydroxide powder were weighed respectively, mixed on a planetary ball mill for 4 h, and then the obtained mixture was put into a sagger, and a first heat treatment was performed under an oxygen atmosphere by roasting at a temperature of 500° C. for 5 h to obtain a first solid material;

[0107] (2) According to the molar ratio of n(Li):n(Ni+Co+Al)=1.05:1, LiOH·H2O and the first solid material were weighed respectively, mixed on a planetary ball mill for 2 hours, and then the obtained mixture was put into a sagger and subjected to a second heat treatment in an oxygen atmosphere by roasting at a temperature of 750°C for 15 hours. The obtained solid product was crushed and sieved to obtain a nickel cobalt aluminum oxide lithium positive electrode material D7 with a chemical formula of LiNi 0.8 Co 0.15 Al 0.05 O2.

[0108] The nickel cobalt aluminum oxide positive electrode material A1 prepared in Example 1 and the nickel cobalt aluminum oxide positive electrode material D1 prepared in Comparative Example 1 were tested by scanning electron microscope. The results are as follows: Figure 2 and 3 shown.

[0109] according to Figure 2 and 3 From the results, it can be seen that the nickel cobalt aluminum oxide lithium positive electrode material A1 has a better spherical morphology; the difference between Comparative Example 1 and Example 1 is only that the order of the mixing step of the aluminum source and the aluminum source and the heat treatment step is different. According to the above, it can be seen that the mixing step of the aluminum source and the cobalt source is performed separately first, and then the heat treatment step is performed, which is beneficial to maintaining the integrity and spherical morphology of the particles.

[0110] The second solid material obtained in step (2) of Example 2 was subjected to scanning electron microscopy testing and element distribution imaging. The results are as follows: Figure 4 shown.

[0111] according to Figure 4 The results show that the nickel element, aluminum element and cobalt element in the second solid material are evenly distributed, which is beneficial to the uniform dispersion of the elements in the subsequent lithiation heat treatment process.

[0112] The nickel cobalt aluminum lithium oxide positive electrode material A2 prepared in Example 2 was subjected to scanning electron microscopy testing and element distribution imaging. The results are as follows: Figure 5 shown.

[0113] according to Figure 5 The results show that the nickel, aluminum and cobalt elements in the nickel cobalt aluminum oxide positive electrode material prepared by the method disclosed in the present invention are evenly distributed.

[0114] X-ray diffraction analysis of nickel cobalt aluminum oxide lithium positive electrode materials A1 and D1-D7 was performed. 003 / I 104 The results of the values ​​are shown in Table 1 below.

[0115] Table 1

[0116] Example / Comparative Example Sample No. <![CDATA[I 003 / I 104 Value of]]> Example 1 A1 1.231 Comparative Example 1 D1 1.112 Comparative Example 2 D2 1.154 Comparative Example 3 D3 1.125 Comparative Example 4 D4 1.197 Comparative Example 5 D5 1.093 Comparative Example 6 D6 1.013 Comparative Example 7 D7 1.105

[0117] The intensity ratio of (003) crystal plane and (104) crystal plane in X-ray diffraction pattern is 003 / I 104 The value of can be used to illustrate the degree of Li / Ni mixing, I 003 / I 104 The larger the value, the smaller the Li / Ni mixing degree. According to the data in Table 1 above, under the same other conditions, the Li / Ni mixing degree of the ternary material prepared by the method disclosed in the present invention is low. It can be further known that the mixing order of the materials and the number of heat treatments affect the stability of the layered structure of the final ternary material, thereby affecting the cyclic stability of the material.

[0118] Specifically, the difference between Example 1, Comparative Example 2 and Comparative Example 7 is that the mixing order of the aluminum source and the cobalt source is different. According to the data in Table 1, the mixing order disclosed in the present invention can promote the uniform dispersion of the elements, thereby improving the stability of the layered structure; the difference between Example 1, Comparative Example 1 and Comparative Example 4 is that the number and order of heat treatment are different. According to the data in Table 1, the number and order of heat treatment disclosed in the present invention can prepare a nickel cobalt aluminum oxide lithium positive electrode material with a stable layered structure.

[0119] Test Case

[0120] The electrochemical stability test of the nickel cobalt aluminum oxide positive electrode materials A1, A3, D1, D3-D6 prepared in the examples and comparative examples was carried out, and the specific steps were as follows:

[0121] The positive electrode material, conductive agent (acetylene black) and binder (polyvinylidene fluoride) were weighed in a mass ratio of 8:1:1, and a solvent (N-methylpyrrolidone) was added and mixed evenly. The mixture was coated on aluminum foil and cut into sheets as the positive electrode. The sheets were then mixed with lithium sheets and electrolyte (1 mol·L -1 LiPF6 ethylene carbonate / ethyl methyl carbonate / dimethyl carbonate, mass ratio is 1:1:1) and separator (Celgard2300) are used to form a lithium ion half-cell, and the electrochemical performance test is carried out. The results are as follows Figure 1 , 6 , as shown in 7.

[0122] Performance test conditions: charge and discharge voltage range is 2.75-4.3V; the charge and discharge rate is 0.1C for the first 4 times and 0.5C after the 5th time; the test temperature is 25℃.

[0123] The electrochemical cycle curve of the lithium ion half-cell prepared using the nickel cobalt aluminum oxide positive electrode material A3 prepared in Example 3 is as follows: Figure 1 shown; according to Figure 1 It can be seen that material A3 exhibits higher specific capacity and cycle stability.

[0124] The electrochemical cycle curves of lithium ion half-cells prepared using the nickel cobalt aluminum oxide positive electrode materials A1 and D1 prepared in Example 1 and Comparative Example 1 are as follows: Figure 6 shown; according to Figure 6 It can be seen that compared with D1, A1 exhibits significantly superior discharge specific capacity and cycle retention rate, further indicating that the method of mixing first and then heat treating is beneficial to improving the electrochemical performance of nickel cobalt aluminum oxide lithium positive electrode materials.

[0125] The electrochemical cycle curves of lithium ion half-cells prepared using the nickel cobalt aluminum oxide positive electrode materials D3-D6 prepared in Comparative Examples 3-6 are as follows: Figure 7 shown.

[0126] according to Figure 7 and Figure 1 and 6 It can be seen from the comparison that the lithium-ion battery prepared by the nickel cobalt aluminum oxide positive electrode material prepared by the method disclosed in the present invention has a higher specific capacity and better cycle stability.

[0127] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0128] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0129] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, characterized in that: The method comprises the following steps: S1, performing a first solid phase mixing of nickel hydroxide and an aluminum source to obtain a first solid material; S2, performing a second solid phase mixing of the cobalt source and the first solid material, and performing a first heat treatment on the obtained mixed material under a first oxygen-containing atmosphere to obtain a second solid material; S3, performing a third solid phase mixing of the lithium source and the second solid material, and performing a second heat treatment on the obtained mixed material under a second oxygen-containing atmosphere.

2. The method according to claim 1, wherein: The aluminum source includes one or more of aluminum hydroxide, aluminum oxide, aluminum carbonate, aluminum oxalate and aluminum acetate; The cobalt source includes one or more of cobalt hydroxide, cobalt oxide, cobalt carbonate, cobalt oxalate and cobalt acetate; The lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate.

3. The method according to claim 1, wherein: The first solid phase mixing, the second solid phase mixing and the third solid phase mixing include solid phase ball milling, and the time is 1-5 hours respectively.

4. The method according to claim 1, wherein: In step S2, the first heat treatment method includes calcination, and the conditions of the first heat treatment include: time of 2-8h and temperature of 400-900°C.

5. The method according to claim 1, wherein: In step S3, the second heat treatment method includes roasting, and the conditions of the second heat treatment include: time is 10-20h, and temperature is 600-850°C.

6. The method according to claim 1, wherein: The first oxygen-containing atmosphere and the second oxygen-containing atmosphere are respectively an oxygen atmosphere or an air atmosphere.

7. The method according to claim 1, wherein: The average particle size of the nickel hydroxide is 5-15 μm.

8. A lithium nickel cobalt aluminum oxide positive electrode material prepared by the method according to any one of claims 1 to 7.

9. The lithium nickel cobalt aluminum oxide positive electrode material according to claim 8, wherein: The lithium nickel cobalt aluminum oxide positive electrode material comprises a chemical formula of LiNi 1-x-y Co x Al y O2 particles, 0.6≤1-xy<1,0 <x≤0.2,0<y≤0.2。 10. A lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode comprises the lithium nickel cobalt aluminum oxide positive electrode material as described in claim 8 or 9.

Citation Information

Patent Citations

  • Spherical aluminum-doped nickel cobalt lithium for lithium ion battery and its making method

    CN101262061A

  • High-density lithium ion battery anode material nickel-cobalt lithium aluminate and preparation method thereof

    CN103050686A

  • Preparation method of high-capacity lithium nickel cobalt aluminate

    CN104795556A

  • Method for preparing cathode material lithium nickel cobalt aluminate for lithium ion battery by spray drying

    CN106025179A

  • Method for preparing high-nickel quaternary single crystal positive electrode material by pure solid-phase method

    CN112626606A